SOCIO-ECONOMIC CONSIDERATIONS OF THE AQUACULTURE INDUSTRIES IN CEBU AND SIQUIJOR, CENTRAL VISAYAS, PHILIPPINES - Rica, Rachel Luz V (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
Aquaculture industry has grown globally to fill in the shortage of fish supply from the sea. A study of aquaculture industries in ICRMP sites of Central Visayas was conducted to determine the socio-cultural and economic aspects of aquaculture. Results revealed that 79% of aquaculture systems are in freshwater and brackish ponds with 50% Oreochromis niloticus and 43% Chanos chanos as common cultured species. Ponds are operated by private individuals and conform to the standard culture systems of cultured species. The individuals that were employed in aquaculture industries are those that are living near the aquaculture sites which are mostly hired as caretakers and helpers and basically nonpermanent and on-call basis. In spite of their employment in the aquaculture industries, communities near aquaculture sites are considered poor since majority of households are living below the poverty thresholds. There is a periodicity of consumption of aquaculture products in the community. The frequency of consumption is high during harvest time (50%) which usually happens every 3-4 months only, thus creating high demand in the community.